Marketing Strategies Through Social Media to Increase the Interest of Prospective Students - Damayanti, Imeliana Wendy; Kusumaningrum, Desi Eri (Universitas Negeri Malang, 2024)
Marketing strategies through social media have become one of the effective approaches in increasing the interest of prospective students in educational institutions. This study aims to analyze various marketing strategies used by schools or educational institutions through social media, as well as their impact on increasing the interest of prospective students. The research method used is a literature study by examining various journals, books, and articles related to digital marketing, social media, and the education sector. From the results of the study, it was found that the optimal use of social media, such as the use of interesting content, improves the reputation of educational institutions. In addition, social media also plays a role in building trust and closeness with prospective students and parents. The results of this research are expected to provide guidance for educational institutions in designing effective marketing strategies to attract the interest of prospective new students.